Antegrade Interlocking Intramedullary Nailing: Biomechanical Investigation - H. farahpour; M. Zoroufi; A.A. Ziaei-Moayyedi (Afarand Scholarly Publishing Institute, 2009)
Introduction : Interlocking has been widely accepted for treatment of femoral shaft fracture. However, complications still exist. Numerous investigations have been carried out on earlier phase of fracture healing with interlocking nail.   Purpose : In this research, a three dimensional model of bone with antegrade interlocking nail in post fracture healing phase during gait cycle is studied. Additionally, published results of others, obtained under different boundary condition, are discussed. Stress distribution pattern in femur with dynamised nail and static nail are investigated.   Results : Three dimensional model of the third generation composite femur was considered in which simple stainless steel Gross Kempf femoral nail was inserted in the medullary canal. Simulation was performed with the assistance of Abaqus analysis finite element codes. Two different loading patterns were used in simulations: Simple loading pattern, and Full muscle loading.   Discussion : Results were verified through simple analytical beamcolumn model. Good agreement between analytical and numerical results was found. Results proved the importance of exact boundary conditions for interlocked femoral nail testing and simulation. Fifty percent increase in bone stress level after removal of proximal screw was observed.